2018
DOI: 10.1007/s12182-018-0247-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors affecting on viscosity reduction of sludge from Iranian crude oil storage tanks

Abstract: Crude oil is a kind of water/oil emulsion, which the oil phase consists of organic molecules with different molecular weights such as alkanes, paraffin, asphaltene, and resins. Due to the change in physicochemical conditions during the production, transportation, storage, and refining, heavier molecules can precipitate from crude oil. Thus, viscous sludge formed at the bottom of storage tanks can cause many problems including reduction of storage capacity of tank, oil contamination, corrosion, repair costs, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Furthermore, an increase in the surfactant concentration resulted in a corresponding increase in emulsion stability. Hassanzadeh et al [79] investigated the influence of factors such as surfactant types, solvents, temperature, pressure, and mixing conditions on emulsions prepared from crude oil storage tanks on Khang Island, Iran. The findings revealed that adjusting the investigated factors could significantly decrease the emulsion viscosity.…”
Section: Parameters Used For the Emulsification Formation Processmentioning
confidence: 99%
“…Furthermore, an increase in the surfactant concentration resulted in a corresponding increase in emulsion stability. Hassanzadeh et al [79] investigated the influence of factors such as surfactant types, solvents, temperature, pressure, and mixing conditions on emulsions prepared from crude oil storage tanks on Khang Island, Iran. The findings revealed that adjusting the investigated factors could significantly decrease the emulsion viscosity.…”
Section: Parameters Used For the Emulsification Formation Processmentioning
confidence: 99%
“…The output of oily sludge is increasing year by year. According to statistics, the total amount of oily sludge produced in the world every year reaches 60 million tons [1][2][3], and with the deep development of most oil fields, the output of oily sludge will continue to increase. According to the source, oily sludge can be divided into oilfield oily sludge (OOS), storage and transportation oily sludge (STOS), refinery oily sludge (ROS), and accidental oily sludge (AOS).…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltenes are a class of polycyclic aromatic hydrocarbon compounds in crude oil, insoluble in paraffin medium, such as n-heptane, easily soluble in aromatic crude oil and organic solvent such as o-xylene [ 1 , 2 ]. The natural asphaltenes in heavy oil tend to accumulate in the crevices of rock and they can also be blocked in wellbore tubing and other equipment [ 3 , 4 ], which greatly reduces the oil recovery rate [ 5 ] and increases the cost of oil displacement in the oil industry [ 6 , 7 , 8 ]. In heavy crude oil, there are many types of asphaltenes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%